Investigating Potential Socioeconomic and Behavioral Factors Influencing Mosquito Net Ownership in Three Countries in Sub-Saharan Africa - Pope, Benjamin (The University of Arizona., 2014)
Malaria was responsible for 207 million illnesses per year, as of 2012. One of the main methods used to combat the mosquito-borne malaria is the use of mosquito nets. Many previous studies have examined various factors affecting malaria incidence and bed net ownership and usage, but few have made cross-country comparisons. In this study we used multilevel hierarchical regression to examine the factors which affect net ownership in Kenya, Malawi, and Tanzania by simultaneously accounting for effects at the individual household and regional levels. Some of the factors identified include wealth index and bicycle ownership (p-values less than 0.05). In Malawi, an effect modification between bicycle ownership and altitude was observed, so the models were stratified by bicycle ownership.